Are banks affected by their holdings of government debt? - Chiara Angeloni; Guntram B. Wolff (Bruegel, 2012)
Banking and sovereign risk in the euro area are highly correlated. This working paper sheds light on the link. We study the stock market performance and the holdings of government debt of the banks stress tested by the European Banking Authority in July and December 2011. Banks' holdings of the sovereign bonds of vulnerable countries generally decreased during the period December 2010 to September 2011. The average stock market performance of each country's banks was very uneven. The European Central Bank's long-term refinancing operation (LTRO) had no material effect on banks' stock market values in the countries under consideration. Greek debt holdings had an effect on banks' market values in the period July to October 2011. After October, this effect disappeared. Holdings of Italian and Irish debt had a material effect on banks' market value in the period October to December 2011. Holdings of debt of other periphery countries, in particular Spain, were not an issue. The July PSI deal did not substantially affect the risk resulting from holdings of debt other than Greek debt. The location of banks matters for their market value. This highlights the need to form a banking union in the euro area.
Keywords: 330; Länderrisiko; Bankrisiko; Öffentliche Anleihe; Kreditderivat; Bankrechnungslegung; EU-Staaten